2011
DOI: 10.1007/s00595-011-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical treatment of advanced follicular thyroid carcinoma with tumor thrombus infiltrating the superior vena cava: report of a case

Abstract: We report a case of advanced follicular thyroid carcinoma with massive involvement of the great veins of the cervix and mediastinum, and extensive tumor thrombus growing intraluminally into the superior vena cava. The patient, a 70-year-old Japanese woman, was treated successfully by a cooperative surgical team of endocrine and cardiovascular surgeons. Total thyroidectomy with thrombectomy was performed via a minimum phlebotomy in the right brachiocephalic vein, sacrificing only the right internal jugular vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Koike et al [9] reported that the various tumor pathologies may explain the different paths of tumor invasion to a great vein. Only a few reports have shown thyroid cancer patients with tumor thrombus that progress to the innominate vein, SVC, and intracranial sigmoid sinus beyond the internal jugular vein [1], [9], [10], [11]. Yamagami et al [12] reported a case of thyroid cancer with extensive tumor thrombus in the atrium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Koike et al [9] reported that the various tumor pathologies may explain the different paths of tumor invasion to a great vein. Only a few reports have shown thyroid cancer patients with tumor thrombus that progress to the innominate vein, SVC, and intracranial sigmoid sinus beyond the internal jugular vein [1], [9], [10], [11]. Yamagami et al [12] reported a case of thyroid cancer with extensive tumor thrombus in the atrium.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with tumor thrombus in the SVC often show the SVC syndrome [1], [13]. Detection of tumor thrombus is important for the planning of operative procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occasionally, both high-risk papillary and follicular thyroid cancer invade great vessels of neck and upper mediastinum ( 10 - 13 ), but in rare occasions tumor embolism can affect remote anatomical sites such as middle cerebral artery ( 50 ). Clinical presentation in great cervical veins can vary from asymptomatic presentation to florid superior vena cava syndrome ( 51 - 54 ). Nine out of 5,507 thyroidectomized thyroid malignancies had tumor thrombi ( 55 ).…”
Section: Resultsmentioning
confidence: 99%